Cultures of Citizenship in the Twenty-First Century Literary and Cultural Perspectives on a Legal Concept - Evans, Vanessa; Banerjee, Mita (Edition Kulturwissenschaft, 2023)
In the early twenty-first century, the concept of citizenship is more contested than ever. As refugees set out to cross the Mediterranean, European nation-states refer to »cultural integrity« and »immigrant inassimilability,« revealing citizenship to be much more than a legal concept. The contributors to this volume take an interdisciplinary approach to considering how cultures of citizenship are being envisioned and interrogated in literary and cultural (con)texts. Through this framework, they attend to the tension between the citizen and its spectral others - a tension determined by how a country defines difference at a given moment.